2020
DOI: 10.1007/s00213-020-05556-2
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal fluoxetine exposure disrupts the circadian response to a phase-shifting challenge in female rats

Abstract: Rationale Selective serotonin reuptake inhibitor (SSRI) antidepressants are increasingly prescribed during pregnancy. Changes in serotonergic signaling during human fetal development have been associated with changes in brain development and with changes in affective behavior in adulthood. The suprachiasmatic nucleus (SCN) is known to be modulated by serotonin and it is therefore assumed that SSRIs may affect circadian rhythms. However, effects of perinatal SSRI treatment on circadian system functioning in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…These results suggest that Flx exposure or 5-HT manipulation during development may promote disruption on internal circadian synchronisation between components of CTS (Kiryanova et al, 2013;Kiryanova et al, 2017;Houwing et al, 2020; see review Morrison et al, 2005) or disruption in the integrity of the SCN itself, which would induce a rearrange of the circadian cycle and gradual desynchronisation in various brain regions (Ehlers et al, 1993;Landgraf et al, 2016;reviewed by Colwell, 2021), including those related to emotional and cognitive behaviour. The integrity of brain areas may affect the parameters of circadian rhythmicity, which is related to changes in the expression of the rest-activity rhythm (Gorka et al, 1996;Tahara & Shibata, 2018;Xie et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These results suggest that Flx exposure or 5-HT manipulation during development may promote disruption on internal circadian synchronisation between components of CTS (Kiryanova et al, 2013;Kiryanova et al, 2017;Houwing et al, 2020; see review Morrison et al, 2005) or disruption in the integrity of the SCN itself, which would induce a rearrange of the circadian cycle and gradual desynchronisation in various brain regions (Ehlers et al, 1993;Landgraf et al, 2016;reviewed by Colwell, 2021), including those related to emotional and cognitive behaviour. The integrity of brain areas may affect the parameters of circadian rhythmicity, which is related to changes in the expression of the rest-activity rhythm (Gorka et al, 1996;Tahara & Shibata, 2018;Xie et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown the long-lasting behavioural impairments induced by early exposure to SSRIs during development in adolescent and adult offspring (for review, see Gemmel et al, 2019), mainly reporting controversial results about anxiety levels, depressivelike symptoms or impairments on memory in males and females. Concerning disruption in circadian rhythms, to the best of our knowledge, a few studies have reported circadian alterations in animals exposed to fluoxetine during development (Houwing et al, 2020;Kiryanova et al, 2013Kiryanova et al, , 2017. These authors have shown that such exposure leads to larger light-induced phase advances, smaller phase advances in response to serotonergic agonists during the midsubjective day and shorter free-running period in constant darkness in male mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dose of fluoxetine was based on previous literature comparing fluoxetine blood levels of humans and animal (Lundmark et al, 2001;Olivier et al, 2011). The same dosage was used in previous experiments (Heinla et al, 2020a;Houwing et al, 2020a;Houwing et al, 2019;Houwing et al, 2020b). Near the end of pregnancy, dams were checked twice per day (9:00 h and 15:00 h) for pup delivery.…”
Section: Breeding and Antidepressant Treatmentmentioning
confidence: 99%